Analisis Peningkatan Kreativitas Siswa Melalui Bimbingan Belajar Berbasis Pembuatan Alat Peraga Sederhana Pada Program KKN Berdampak di Desa Siamporik Dolok - Ainun Mardiyah Lubis; Kholid Umar; Laila Tussifah Lubis; Darwis Lubis; Rosa Amelia Siagian; Elisa Ariani (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2026)
Student creativity is an essential component in supporting meaningful and engaging learning processes, particularly at the elementary school level. However, learning activities are often still teacher-centered and lack the use of instructional media that stimulate student creativity. This study aimed to analyze the improvement of students’ creativity through tutoring activities based on the creation of simple teaching aids during the Impactful Community Service Program (KKN Berdampak) in Siamporik Dolok Village, Angkola Selatan District, South Tapanuli Regency. The study employed a descriptive quantitative approach supported by qualitative data. Participants were elementary school students involved in tutoring activities conducted by KKN students. Data were collected through structured observations and documentation. Students’ creativity was assessed using five indicators: generating creative ideas, suitability of teaching aids to learning materials, activeness in the creation process, ability to modify recycled materials, and group collaboration. Observations were conducted before and after the tutoring activities. The results showed an improvement in students’ creativity across all indicators, with the average creativity score increasing from 2.14 before the activity to 3.50 after the activity. Students demonstrated greater creativity in generating ideas, higher participation in learning activities, improved collaboration skills, and enhanced ability to utilize recycled materials as educational teaching aids. These findings indicate that tutoring activities based on the creation of simple teaching aids are effective in enhancing students’ creativity and support the objectives of the Impactful KKN program in fostering a smart, creative, and productive community.